2020
DOI: 10.1038/s41598-020-76750-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling and weighted gene co-expression network analysis of early floral development in Aquilegia coerulea

Abstract: The earliest phases of floral development include a number of crucial processes that lay the foundation for the subsequent morphogenesis of floral organs and success in reproduction. Currently, key transcriptional changes during this developmental window have been characterized in the model species Arabidopsis thaliana, but little is known about how transcriptional dynamics change over the course of these developmental processes in other plant systems. Here, we have conducted the first in-depth transcriptome p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 91 publications
(113 reference statements)
0
10
0
Order By: Relevance
“…Previous transcriptomic sequencing in young A. coerulea FMs indicated that the expression of AqWUS is maintained during the developmental stages equivalent to TP1 through TP3 in the current study, with expression dropping rapidly to undetectable levels during the developmental stages equivalent to TP4 to TP6 (Min and Kramer, 2020). If we examine the central region of the FM (i.e.…”
Section: Cellular Dynamic Change During Fmt In a Coeruleamentioning
confidence: 54%
See 1 more Smart Citation
“…Previous transcriptomic sequencing in young A. coerulea FMs indicated that the expression of AqWUS is maintained during the developmental stages equivalent to TP1 through TP3 in the current study, with expression dropping rapidly to undetectable levels during the developmental stages equivalent to TP4 to TP6 (Min and Kramer, 2020). If we examine the central region of the FM (i.e.…”
Section: Cellular Dynamic Change During Fmt In a Coeruleamentioning
confidence: 54%
“…This observation raises some intriguing questions: why is there an increase in cell division in the central zone when the carpel primordia are initiating, and what is responsible for the pattern? This period also appears to correspond with the onset of FMT based on the decline in AqWUS expression (Min and Kramer, 2020), so is this the last flush of CZ cell divisions or are the divisions related more directly to initiation of the carpel primordia? Answering these questions will require a better understanding of how AqWUS downregulation is controlled in Aquilegia, particularly the nature of any 'timer mechanism' regulating the number of cell divisions before FMT.…”
Section: Cellular Dynamic Change During Fmt In a Coeruleamentioning
confidence: 99%
“…Meristematic structures, which are often too large and dense for meaningful 3D imaging using fluorescence or EM, can greatly benefit from XRM. Numerous recent studies have provided important insights into meristematic and inflorescence structure development, including S. viridis ( Yang et al, 2018 ), Hordeum vulgare ( Walla et al, 2020 ), maize ( Teng et al, 2020 ), Aquilegia coerulea ( Min and Kramer, 2020 ), and other grasses ( Kellogg et al, 2013 ; AuBuchon-Elder et al, 2020 ). These examples illustrate the breadth of research questions that can be enhanced by additional tissue- and cell-level 3D XRM imaging to measure and evaluate meristematic structure development over scales not possible or practical with other methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…The exportNetworkToCytoscape package in R was used to calculate the weight of each gene in co-expression modules and generate the edges file to select the top 300 genes in each module [25]. Genes with degrees greater than 25 were considered hubs.…”
Section: Weighted Gene Co-expressed Network Analysismentioning
confidence: 99%